2018
DOI: 10.3846/jcem.2018.447
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of Destruction Mechanism of Polymeric Intumescent Fire Protective Coatings

Abstract: Abstract. The article describes the destruction mechanism of intumescent fire protective paint coatings at the time of their aging under the impact of simulated climatic factors. Steel plates covered in anti-corrosion varnishes and intumescent fire protective paint coatings of several types and different composition were used in the research, while certain samples were also additionally covered in protective coatings protecting from environmental effects. SEM, DTA and FT-IR researches were conducted on control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Despite their versatility, manufacturability in the application, aesthetic characteristics, intumescent-type coatings have a series of disadvantages. First of all, it is low atmosphere resistance [3] and resistance to aggressive environments [4], and, accordingly, a limited service life [5]. The authors of work [6], for example, found that after 30 years of natural aging under the climatic conditions of Italy, intumescent coatings lose their fire protection functions completely.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite their versatility, manufacturability in the application, aesthetic characteristics, intumescent-type coatings have a series of disadvantages. First of all, it is low atmosphere resistance [3] and resistance to aggressive environments [4], and, accordingly, a limited service life [5]. The authors of work [6], for example, found that after 30 years of natural aging under the climatic conditions of Italy, intumescent coatings lose their fire protection functions completely.…”
Section: Introductionmentioning
confidence: 99%
“…This is primarily due to the lack of procedures for modeling the conditions of artificial aging for a coating. There are also no adequate criteria for determining the fire-protective properties of the coating after aging, followed by forecasting its service life [4,5]. National and international standards, for example [20], to some extent define methodological approaches to determining the durability of reactive coatings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation